Competition intensity and fatigue in elite fencing - Turner, A. N.; Kilduff, L. P.; Marshall, G. J. G.; Phillips, J.; Noto, A.; Buttigieg, C.; Gondek, M.; Hills, F. A.; Dimitriou, L. (The Journal of Strength and Conditioning Research, 2017)
As yet, no studies have characterized fencing competitions. Therefore, in elite male foilists and across 2 competitions, we investigated their countermovement jump height, testosterone (T), cortisol (C), alpha-amylase (AA), immunoglobulin A (IgA), heart rate (HR), blood lactate (BL), and rating of perceived exertion (RPE). Average (±SD) scores for RPE, BL, and HR (average, max, and percentage of time =80% HRmax) were highest in the knockout bouts compared with poules (8.5 ± 1.3 vs. 5.7 ± 1.3, 3.6 ± 1.0 vs. 3.1 ± 1.4 mmol/L, 171 ± 5 vs. 168 ± 8 b/min, 195 ± 7 vs. 192 ± 7 b/min, 74 vs. 68%); however, only significant (p = 0.05) for RPE. Countermovement jump height, albeit nonsignificantly (p > 0.05), increased throughout competition and dropped thereafter. Although responses of C, AA, and IgA showed a tendency to increase during competition and drop thereafter (T and T:C doing the opposite), no significant differences were noted for any analyte. Results suggest that fencing is a high-intensity anaerobic sport, relying on alactic energy sources. However, some bouts evoke BL values of =4 mmol·L and thus derive energy from anaerobic glycolysis. High HRs appear possible on account of ample within- and between-bout rest. The small competition load associated with fencing competitions may explain the nonsignificant findings noticed.